Ma’A Lexicon and Afro-Asiatic IV: Ma’A ŝ- - Takács, Gábor (Lingua Posnaniensis, 2010)
The paper represents part of a longer series that examines the lexical stock of the Ma'a language, an exotic Mischsprache combining a Bantu grammar with a basically Cushitic (henceforth, Afro-Asiatic) lexicon, from the standpoint of etymology. This part contains (mostly new) etymologies of Ma'a words with the initial lateral sibilant.